Antioxidant Effects of the Quercetin in the Jejunal Myenteric Innervation of Diabetic Rats - de Souza, Sara R. Garcia; de Miranda Neto, Marcílio Hubner; Martins Perles, Juliana Vanessa Colombo; Vieira Frez, Flávia Cristina; Zignani, Isabela; Ramalho, Francielle Veiga; Hermes-Uliana, Catchia; Bossolani, Gleison Daion Piovezana; Zanoni, Jacqueline Nelisis (Frontiers in Medicine, 2017)
Purpose: Enteric glial cells (EGC) exert a critical role in the structural integrity, defense and metabolic function of enteric neurons. Diabetes mellitus (DM) is a chronic disease characterized by metabolic disorders and chronic autonomic neuropathy. Quercetin supplementation, which is a potent antioxidant, has been used in order to reduce the effects of diabetes-induced oxidative stress. The purpose of this research was to investigate the effects of quercetin supplementation in the drinking water at a daily dose of 40 mg on the glial cells and neurons in the jejunum of diabetic rats. Material and Methods: Twenty 90-day-old male adult Wistar rats were split into four groups: normoglycemic control (C), normoglycemic control supplemented with quercetin (Q), diabetic (D) and diabetic supplemented with quercetin (DQ). After 120 days, the jejunums were collected and immunohistochemical technique was performed to label S-100-immunoreactive glial cells and HuC/D-immunoreactive neurons. Results: An intense neuronal and glial reduction was observed in the jejunum of diabetic rats. Quercetin displayed neuroprotective effects due to reduced cell body areas of neurons and glial cells in Q and DQ groups compared to their controls (C and D groups). Interestingly, quercetin prevented the glial and neuronal loss with a higher density for the HuC/D-immunoreactive neurons (23.06%) and for the S100-immunoreactive glial cells (14.55%) in DQ group compared to D group. Conclusion: Quercetin supplementation promoted neuroprotective effects through the reduction of neuronal and glial body areas and a slight prevention of neuronal and glial density reduction.